Membangun Ekonomi Islam Dengan Melestarikan Lingkungan (Menanam Sayur Organik Dan Budidaya Lele Organik) - Anip Dwi Saputro (Jurnal Ekonomi, 2016)
Islam in strengthening the social orientation among Muslims, then he introduced the concept of an obligation together, in which individual responsibility can be done by other individuals. This is called the fardhu kifayah. This concept emphasizes meeting the needs of society and urge individuals to strive to fulfil them. With farming and organic farming catfish will create food and financial independence for Muslim families in order to achieve economic independence Islam halalan thoyiban. By utilizing the land around our house for use as land to grow crops or raise livestock organically catfish will be generated increase in financial income and food security are highly nutritious. It will be directly proportional to the increase in the welfare of Muslim families which have been considered weak and be able to build Islamic economic independence significantly in the society. Based on the survey we did in society in general, the need for organic vegetables and organic catfish has been felt at the increasing demand of today's society. With the increasing prevalence of information is growing, people are now faced with the basic necessities of food is good and healthy for their families. People are starting to think and act real to abandon the use of chemicals that enter the intake of food that they consume every day.